STRATEGI KEMANDIRIAN INDUSTRI PETROKIMIA NASIONAL - Situmorang, Sirma Oktaviani (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2026)
This study analyzes Indonesia’s petrochemical industry dependence on imports and formulates policy strategies to strengthen domestic industrial independence. Using a qualitative policy analysis approach combined with descriptive-comparative analysis, this research utilizes secondary data from international institutions, national statistics, and peer-reviewed journals (last 5 years). The findings show that Indonesia faces structural constraints including high feedstock prices, limited upstream–downstream integration, infrastructure gaps, and dependence on global supply chains. Comparative evidence from ASEAN and East Asia demonstrates that integrated industrial policy, energy pricing reform, and scale investment are key determinants of competitiveness. The study recommends refinery–petrochemical integration, gas pricing reform, fiscal incentives, and industrial cluster development. These measures are expected to reduce import dependency and strengthen industrial resilience.